Design Principles and Performance Analysis of a Wimshurst Generator - Ege, M. Bekir; Font, Aytug; Bolat, Suna; Kalenderli, Ozcan (IEEE, 2014)
Wimshurst generator is an electrostatic machine that produces high DC voltages by induction. The class of electrostatic machine that Wimshurst belongs to is influence machines. Because the charges are distributed on the machine by influencing each other to have cumulative charge generation. Two opposite rotating insulator disks with metal sectors on it distribute the charges such a way that, negative charges are collected in one capacitor, positive charges in the other. In this study, a Wimshurst generator is designed and constructed using commonly available materials.
International Conference on High Voltage Engineering and Application (ICHVE) -- SEP 08-11, 2014 -- Poznan, POLAND